NATO and U.S. Ballistic Missile Defense Programs: Divergent or Convergent Paths? - Toms, Kevin E. (2008)
NATO and the United States are actively pursuing missile defense policies. NATO has invested in the Active Layered Theatre Ballistic Missile Defence (ALTBMD) information network to support the Theater Missile Defense (TMD) capabilities of specific Allies for the protection of forward deployed troops, and studies of the feasibility and political-military implications of Ballistic Missile Defense (BMD) for the protection of NATO territory, forces and population centers. The U.S. program includes TMD activities in cooperation with NATO Allies, such as Patriot, as well as BMD research and deployment. The U.S. proposal to deploy BMD system elements in Poland and the Czech Republic has led to more extensive discussions of BMD in the Alliance. The North Atlantic Council made BMD-relevant decision in April 2008. The United States and its NATO Allies nonetheless seem to differ greatly on the urgency and importance of pursuing BMD. TMD generates far more cooperation and support within the Alliance than does BMD for the protection of NATO territory, forces and population centers. This thesis compares TMD and BMD policies within the Alliance in an attempt to identify the causes of disagreements on BMD policy and to propose a course of action that may meet the Alliance's goals.